Current EC-US economic conflicts - Dieter Lösch (Intereconomics, 1984)
The danger of serious disagreements on the agricultural question and a trade war developing between the EC and the USA may never have been as great as it is today: on the one hand, the EC has less and less leeway for its foreign trade policy because the problems in financing its agricultural policy are still unsolved and, on the other hand, no major concessions can be expected of the Reagan administration in an election year. Yet agriculture is only one of a series of fields of economic activity where Euro-American collisions are continually occurring.
Keywords: 330; Foreign Trade